Antibiotic optimization in the difficult-to-treat patient with complicated intra-abdominal or complicated skin and skin structure infections: focus on tigecycline - Wanda C Reygaert (Dove Medical Press, 2010)
Wanda C ReygaertDepartment of Biomedical Sciences, Oakland University William Beaumont School of Medicine, Rochester, MI, USAAbstract: Complicated intra-abdominal and skin and skin structure infections are widely varied in presentation. These infections very often lead to an increase in length of hospital stay, with a resulting increase in costs and mortality. In addition, these infections may be caused by a wide variety of bacteria and are often polymicrobial with the possibility of the presence of antimicrobial-resistant strains, such as methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, extended-spectrum β-lactamase strains (Escherichia coli, Klebsiella pneumoniae), and K. pneumoniae carbapenemase-producing strains. In combination with patients’ immunosuppression or comorbidities, the treatment and management options for initial therapy success are few. Tigecycline, a new glycylcyline antimicrobial from the tetracycline drug class, represents a viable option for the successful treatment of these infections. It has been shown to have activity against a wide variety of bacteria, including the antimicrobial-resistant strains. As with all tetracycline drugs, it is not recommended for pregnant or nursing women. The potential side effects are those typical of tetracycline drugs: nausea, vomiting, and headaches. Drug–drug interactions are not expected, and renal function monitoring is not necessary.Keywords: complicated intra-abdominal infections, complicated skin and skin structure infections, tigecycline